Tinjauan Al-Qur'an Dan Hadist tentang Etos Kerja (Studi Literatur) - Mulyadi, Nepi; Reinaldo, Antonio; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The presence of religion is often a source of inspiration for individuals in various aspects of life, including in the world of work. This article explores the verses of the Koran and the hadiths of the Prophet Muhammad that relate to work ethic. This research aims to present an understanding of the Islamic view of hard work, dedication, and responsibility in carrying out the profession. Using text analysis methods, relevant verses and hadiths were studied to explore the values ​​that encourage individuals to have a high work ethic in the view of the Islamic religion. The findings from this research provide insight into how religious teachings can serve as moral and spiritual guidance in increasing productivity and quality of work in Muslim societies. The implications of these findings are also discussed to strengthen the link between religious values ​​and the world of work in the contemporary context.